Features of the Formation and Implementation of a Package of Economic Reforms in Ukraine and its Regions (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The article attempts to substantiate the periodization of Ukrainian economic reforms in Ukraine over the period of staying on the posts of Ukrainian presidents. The main content of economic reforms at the national and regional levels at each stage is formulated. The package was formed and blocks of related economic reforms – institutional, financial, agrarian and industrial sectors, infrastructure, the sector of foreign economic activity, socially oriented, energy and ecologically oriented – were allocated. The characteristics of citizens' awareness of the content of certain economic reforms and their assessment of the effectiveness of reforms are presented. The subjects of reforms (the National Council of Reforms, the executive committee of reforms, the target team of reforms, the project office) are outlined and their functional responsibilities are outlined. The peculiarities of management of business process of economic reforms in modern conditions are considered. Stages, processes and corresponding measures on reforming the economy of the country and its regions are established. The key indicators of the effectiveness of economic reforms in general and in the context of individual reforms are determined.
Keywords: economic reforms, package of reforms, periodization of reforms, business process of reforms, management of reforms, evaluation of the effectiveness of reforms.